The boundaries of belonging and the boundaries of safety - Segrave, Marie Therese (The borders of violence, 2024)
In the concluding chapter, we present the core theoretical and conceptual layers that are woven throughout this book. We identify the ways we have sought to meet the ambitious objectives of this project and consider the implications for how we do research and how we can meet the conceptual, theoretical and policy challenges that our analysis brings to the fore. As we discussed, the approach we take to the analysis presented in this book is not intended to be exclusive or definitive. Instead, we wish to lay the ground for ongoing critical analysis and recognition that even responses that are framed as protective are part of a system that is both exclusionary and violent. In the accounting for men's violence and the violence of families enacted against women, we argue that the border and the migration system must be foregrounded in efforts to recognise what sustains this violence. Absent this, no measures will be effective in addressing the conditions that contribute to and reproduce violence against women on temporary visas.